Internationalizing Arabic Language Materials in Pesantren Education: An ACTFL-Based Evaluation of Durusullughah al Arabiyah - Mahdi Wahyuni Salam; Iswan Fadlin; Tulus Musthofa (Journal of Arabic Language Learning and Teaching (JALLT), 2026)
Despite the growing importance of international proficiency standards in foreign language education, studies evaluating Arabic textbooks in pesantren contexts using the ACTFL framework remain scarce. This study examines the alignment of Durusullughah al Arabiyah, a textbook used at Pesantren Almuslim, with ACTFL proficiency standards across listening, speaking, reading, and writing skills. Employing a qualitative content analysis approach, the study analyzed communicative functions, proficiency levels, and pedagogical patterns embedded in the textbook using ACTFL descriptors. The findings reveal that the textbook largely corresponds to the ACTFL Novice Mid level, as reflected in its contextual vocabulary, simple dialogues, drill-based exercises, and communicative tasks related to learners’ daily experiences. The Direct Method employed in the textbook supports the gradual development of basic communicative competence through repetitive and contextualized language practice. However, instructional activities remain predominantly teacher-centered and rely heavily on controlled communication, providing limited opportunities for interpretive interaction and spontaneous language production. The study highlights the potential compatibility between pesantren-based Arabic language pedagogy and international proficiency frameworks. It contributes to the advancement of Arabic textbook evaluation grounded in global standards while extending ACTFL-related scholarship within the context of Islamic boarding school education.